2014
DOI: 10.1590/s1415-43662014000600001
|View full text |Cite
|
Sign up to set email alerts
|

Nodulação e crescimento do feijoeiro em resposta à aplicação de molibdênio e inoculante rizobiano

Abstract: R E S U M OO feijoeiro (Phaseolus vulgaris) possui a capacidade de se beneficiar da fixação biológica de nitrogênio; entretanto, o sucesso deste processo é influenciado por diversos fatores. O objetivo deste trabalho foi dimensionar a magnitude da contribuição do molibdênio (fontes e doses) e rizóbios (nativos e introduzidos) para nodulação, acúmulo de nitrogênio e crescimento do feijoeiro IPR 139. O experimento foi realizado no ano de 2011 em casa de vegetação, no delineamento inteiramente casualizado em esqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…Such variability in symbiotic system which has the ability of collections of rhizobia, is a result of high biodiversity of these microorganisms, associated with biotic and abiotic factors. Studies have shown that the symbiotic association is affected by several factors such as soil acidity, aluminum toxicity (Campanharo et al, 2010), salinity (Medeiros et al, 2008), low soil fertility (Sulieman and Tran, 2015), phosphorus and molybdenum deficiency (Matoso and Kusdra, 2014), high soil temperatures (Ferrari et al, 1967) and low water availability in the soil (Andres et al, 2012). The use of microsymbionts adapted to different environmental conditions, combined with the correction of factors related to soil fertility, which may potentiate the effects of inoculation with diazotrophic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Such variability in symbiotic system which has the ability of collections of rhizobia, is a result of high biodiversity of these microorganisms, associated with biotic and abiotic factors. Studies have shown that the symbiotic association is affected by several factors such as soil acidity, aluminum toxicity (Campanharo et al, 2010), salinity (Medeiros et al, 2008), low soil fertility (Sulieman and Tran, 2015), phosphorus and molybdenum deficiency (Matoso and Kusdra, 2014), high soil temperatures (Ferrari et al, 1967) and low water availability in the soil (Andres et al, 2012). The use of microsymbionts adapted to different environmental conditions, combined with the correction of factors related to soil fertility, which may potentiate the effects of inoculation with diazotrophic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Bhuiyan et al (2008) and Togay, Togay and Dogan (2008a) obtained maximum seed yield and aboveground biomass production of mung bean and lentils, respectively, after using phosphorus application rates associated with molybdenum fertilization. Fertilization with P and Mo also had a positive effect on edible bean and soybean yield in areas of the Brazilian Cerrado (Araújo et al, 2009;Matoso;Kusdra, 2014;Vieira et al, 2016;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These data show that the biological nitrogen fixation may supplement the nitrogen fertilization in the bean crop, allowing a reduction in nitrogen fertilizer rates, without losses in grain yield. Nevertheless, Matoso and Kusdra [16] did not find positive results regarding the inoculation of common bean with R. tropici.…”
Section: Table 2 Population Of Plants Per Hectare Mean Pod Length (mentioning
confidence: 93%